2015
DOI: 10.1155/2015/856091
|View full text |Cite
|
Sign up to set email alerts
|

Enteral L-Arginine and Glutamine Supplementation for Prevention of NEC in Preterm Neonates

Abstract: Objective. Evaluating the efficacy and safety of arginine and glutamine supplementation in decreasing the incidence of NEC among preterm neonates. Methods. Prospective case-control study done on 75 preterm neonates ≤34 weeks, divided equally into L-arginine group receiving enteral L-arginine, glutamine group receiving enteral glutamine, and control group. Serum L-arginine and glutamine levels were measured at time of enrollment (sample 1), after 14 days of enrollment (sample 2), and at time of diagnosis of NEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
(41 reference statements)
1
17
0
Order By: Relevance
“…As TLR-2 and TLR-4 have established roles in inducing synthesis of inflammatory mediators and increasing apoptosis in NEC [52][53][54], their reduced expression by glutamine supplementation suggests a mechanism by which it mediates protection. In a small study that evaluated the outcomes of arginine and glutamine supplementation in 25 preterm neonates of less than 34 weeks' gestation, there were no infants that developed NEC in the glutamine group and no difference in the NEC incidence in the arginine group [55]. However, large RCTs of infants diagnosed with severe gastrointestinal disease, including NEC, spontaneous intestinal perforation, and intestinal structural anomalies, did not show a decreased risk of death or severe infections while receiving enteral glutamine [56].…”
Section: Glutaminementioning
confidence: 99%
“…As TLR-2 and TLR-4 have established roles in inducing synthesis of inflammatory mediators and increasing apoptosis in NEC [52][53][54], their reduced expression by glutamine supplementation suggests a mechanism by which it mediates protection. In a small study that evaluated the outcomes of arginine and glutamine supplementation in 25 preterm neonates of less than 34 weeks' gestation, there were no infants that developed NEC in the glutamine group and no difference in the NEC incidence in the arginine group [55]. However, large RCTs of infants diagnosed with severe gastrointestinal disease, including NEC, spontaneous intestinal perforation, and intestinal structural anomalies, did not show a decreased risk of death or severe infections while receiving enteral glutamine [56].…”
Section: Glutaminementioning
confidence: 99%
“…8,9,23 ; Richir et al, 24 reported that preterm infants with NEC showed significantly low L-arginine level than those without NEC. Further, Amin et al, 25 who investigate the role of enteral L-arginine supplementation in prevention of NEC, concluded that plasma L-arginine level was significantly low at time of diagnosis of NEC. Regarding CPS1 gene (4217C>A) polymorphism, we disclosed no significant difference in genotypes and allele distribution between preterm cases and preterm controls.…”
Section: Discussionmentioning
confidence: 99%
“…Models of sepsis and gut inflammation have shown decreased uptake of glutamine by enterocytes [35]. Supplementation with glutamine has been studied in prevention of NEC in preterm infants, as it has been found to decrease the possibility of bacterial translocation across enterocytes [36]. The decreased concentration in the antibiotic group may be secondary to increased use in maintenance of the mucosal barrier and in further proliferation of enterocytes ( Figure 6).…”
Section: Amino Acids Critical To Intestinal Metabolismmentioning
confidence: 99%